Nonocclusive Mesenteric Ischaemia Induced by Diltiazem Overdose: A Case Report. Issue 3 (May 2017) - Kim, JW; Park, SO; Hong, DY; Baek, KJ; Lee, KR
Acute mesenteric ischaemia is a rare complication of calcium channel blocker (CCB) overdose. A previous study reported a case of mesenteric ischaemia induced by poisoning with CCBs other than diltiazem. We present a case of nonocclusive mesenteric ischaemia (NOMI) induced by diltiazem poisoning. Through this case report, we wish to emphasize that the clinicians should keep the possibility of intestinal ischaemia in mind from the early phase of calcium channel blocker poisoning. In addition, close monitoring and intense abdominal examination including the abdominal computed tomography scan should be done if CCBs poisoning patients complained of an abdominal pain.